Modeling and Simulation of Hill Side Feasibility with GIS - JOSHUA LING , ZHONG YIE (2010)
Hill Side development has always been a sensitive issue to a development, especially when it involves the public. In Malaysia, the problems and solutions to a sustainable hill side development has been largely discussed over the years while in geotechnical aspect, it is a never ending discussion. Engineering investigations is hard to be predicted and carried out especially at hilly area that is often hard to be reached. Thus, engineering feasibility studies are hard to be carried out and indirectly, it will certainly minimize its accuracy and most often, it is very much dependent on the engineers experience in making feasibility decisio-i. This paper presents an integrated system to improve Hill Side feasibility by modeling and simulation with GIS, the modeling involves, Land Elevation and Land gradients plotting for Hill Land identification and Hydrological mapping in Flow Directions Flow Length and flow accumulation to identify the hydrological effects on the development. The transformation techniques of data into GIS base are Modeled and Simulated. A full and clearer development outlook has been presented. Data from different factors that affecting development is combined and of course in this project, we are focusing on few selected parameters mentioned. Techniques and difficulties of modeling and simulation with a large database are discussed. A user-friendly interface is developed t) support the planning, management and decision making in the development.